What Is the Role of Beta-Agonist Bronchodilators in the Day-to-Day Treatment of Chronic Asthma? - Pierre Ernst (Canadian Respiratory Journal)
The reported links of asthma morbidity and mortality to the use of in haled beta-agonist bronchodilators are reviewed. Reports from the Saskatchewan Asthma Epidemiology Project (SAEP) suggest that it is excessive use that is linked to life-threatening asthma and that patients at highest risk can be identified by their increasing use of these medications. This is the major justification for prescribing short acting beta-agonists on an as needed basis, though there is both clinical and experimental evidence suggesting regular use of these agents may not be beneficial. New longer acting inhaled beta-agonists designed for regular use are being introduced and their exact role remains to be defined. Provisionally, they appear to be useful in patients whose asthma is not well controlled with optimal doses of inhaled corticosteroids. The use of these newer agents for the relief of acute bronchospasm is contraindicated because of their slow onset of action.